2019
DOI: 10.3390/su11020476
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Relationships between Urban Structures and Air Pollution in Korea

Abstract: Urban structures facilitate human activities and interactions but are also a main source of air pollutants; hence, investigating the relationship between urban structures and air pollution is crucial. The lack of an acceptable general model poses significant challenges to investigations on the underlying mechanisms, and this gap fuels our motivation to analyze the relationships between urban structures and the emissions of four air pollutants, including nitrogen oxides, sulfur oxides, and two types of particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 66 publications
(97 reference statements)
2
6
0
Order By: Relevance
“…Previous studies analyzed using the ratio of secondary industry, the area and ratio of industrial area, and the ratio of manufacturing workers, similar to air pollution emission facilities. The results of this study were similar to those of Jung et al [18]. On the other hand, Cho•Choi [31] and Cárdenas Rodríguez et al [8] did not show a significant relationship between NO 2 concentration and emission facility density.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies analyzed using the ratio of secondary industry, the area and ratio of industrial area, and the ratio of manufacturing workers, similar to air pollution emission facilities. The results of this study were similar to those of Jung et al [18]. On the other hand, Cho•Choi [31] and Cárdenas Rodríguez et al [8] did not show a significant relationship between NO 2 concentration and emission facility density.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the number of registered vehicles per capita is an index reflecting not only the quantitative increase of vehicles but also the economic aspect of a region. When it is connected to the economic power improvement of a region or an individual household, it also indirectly supported Jung et al [18], who showed that gross regional domestic product(GRDP) and the NO 2 concentration were positively related.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The Bayesian model can synthesize information from different sources and improve the reliability of inferred conclusions [71,72]. Therefore, when judging the category of a pixel whose difference between the maximum probability value and the second-maximum probability value is small, the spatial structure information of the pixels can be further introduced to improve the reliability of the judgment by using the Bayesian model.…”
Section: Introductionmentioning
confidence: 99%
“…Macpherson et al [27] used a Bayesian network model to analyze wetland protection decision making and management; Richards [28] applied this model to regional adaptation adjustment and early warning under climate change; while Stritih [5] used Bayesian networks to quantify uncertainties in ecosystem services assessment. Jung et al [29] used Bayesian spatial regression models to analyze the relationship between urban structure and air pollution in Korea; Wu et al [30] applied the Bayesian network and other methods to assess the fire risk at underground subway stations; Pérez-Sánchez et al [31] used the Bayesian model to evaluate the hydrological model of water resources in the Spanish peninsula. In addition to these studies, Bayesian networks have also been widely used in fishing net construction, water purification, landscape protection and development, and food security [15,25,[32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%